Synthesis and characterization of different transition metal-alginate based heterogeneous catalyst for esterification reaction - Pua F.-L.; Looi K.-T.; Shamala Gowri K.; Sharifah N. (Trans Tech Publications Ltd, 2023)
Alginate; Biodiesel; Esterification; Esters; Iron compounds; Nanotechnology; Oleic acid; Transition metals; Biodiesel production; Esterification of oleic acids; Esterification reactions; Heterogeneous catalyst; High free fatty acids; Homogeneous catalyst; Reaction temperature; Synthesis and characterizations; Catalysts